Religion and economy - Mohammad, Faiz; Haque, Ziaul; Anwar, Mohammad Saeed (The Pakistan development review, 1991)
Three articles (and comments on these articles) on Islamization of the economy under the Martial Law regime of Pakistan, the relationship between religion and economics, introduction of the Zakat system in Pakistan in 1980 and its role in eradicating poverty and inequalities and Islamic financial institutions in Malaysia and their contribution towards socio-economic development of the Muslims of the country. (DÜI-Sen)